Efficient gold(I)/silver(I)-cocatalyzed cascade intermolecular N-Michael addition/intramolecular hydroalkylation of unactivated alkenes with α-ketones - Xiao, Ya-Ping; Liu, Xin-Yuan; Che, Chi-Ming (Beilstein Journal of Organic Chemistry, 2011)
The gold(I)/silver(I)-cocatalyzed cascade intermolecular N-Michael addition/intramolecular hydroalkylation reaction offers a simple and efficient method for the synthesis of pyrrolidine derivatives in moderate to excellent product yields and with moderate to good diastereoselectivities. The reaction conditions and the substrate scope of this reaction are examined, and a possible mechanism involving AgClO4 catalyzed intermolecular N-Michael addition and the subsequent gold(I)-catalyzed hydroalkylation is proposed.
Keywords: cascade; cocatalyzed; gold(I)-catalyzed; intramolecular hydroalkylation; intermolecular N-Michael addition; pyrrolidine; silver(I)-catalyzed